2019
DOI: 10.1111/1462-2920.14746
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics groups phages of Negativicutes and classical Firmicutes despite different Gram‐staining properties

Abstract: Summary Negativicutes are gram‐negative bacteria characterized by two cell membranes, but they are phylogenetically a side‐branch of gram‐positive Firmicutes that contain only a single membrane. We asked whether viruses (phages) infecting Negativicutes were horizontally acquired from gram‐negative Proteobacteria, given the shared outer cell structure of their bacterial hosts, or if Negativicute phages co‐evolved vertically with their hosts and thus resemble gram‐positive Firmicute prophages. We predicted and c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…To comprehensively examine the association of each prophage WO variant with its chromosomal location in Wolbachia , we mapped integration sites, determined by the recombinase or the most 5’- WO gene, on the chromosome with respect to normalized distance from the putative origin of replication, ori [ 61 ]. There is a clustering of prophage WO insertion loci, particularly sr3WO, opposite the putative origin of replication ( Fig 3B ; Chi-square 2-tailed, p = 0.0035) that is similar to the localization patterns of temperate phages in Escherichia , Salmonella , and Negativicutes [ 62 65 ]. WO chromosomal location patterns support a model in which prophage insertions and WO-like Islands may not be tolerated in certain regions of the Wolbachia chromosome, in this case the region directly surrounding the predicted origin of replication.…”
Section: Resultsmentioning
confidence: 72%
“…To comprehensively examine the association of each prophage WO variant with its chromosomal location in Wolbachia , we mapped integration sites, determined by the recombinase or the most 5’- WO gene, on the chromosome with respect to normalized distance from the putative origin of replication, ori [ 61 ]. There is a clustering of prophage WO insertion loci, particularly sr3WO, opposite the putative origin of replication ( Fig 3B ; Chi-square 2-tailed, p = 0.0035) that is similar to the localization patterns of temperate phages in Escherichia , Salmonella , and Negativicutes [ 62 65 ]. WO chromosomal location patterns support a model in which prophage insertions and WO-like Islands may not be tolerated in certain regions of the Wolbachia chromosome, in this case the region directly surrounding the predicted origin of replication.…”
Section: Resultsmentioning
confidence: 72%
“…They are widely distributed in nature and exist in anaerobic habitats, such as aquatic sediment, soil, anaerobic sewage digesters, and animal gastrointestinal tracts. Similarly, Rhodocyclales and Acidaminococcales are also adapted for anaerobic environments (Rands et al, 2019;Wang et al, 2020). These findings indicated that M. bicuspidata infection significantly At the genus level, 37 genera increased significantly, and 21 genera belonged to the phylum Firmicutes, of which 11 genera belonged to the order Eubacteriales, including Hespellia, Acetivibrio, Lachnoanaerobaculum, Youngiibacter, Defluviitalea, Proteocatella, Anaeromassilibacillus, Asaccharospora, Anaerotruncus, Geosporobacter, and Anaerotignum.…”
Section: Discussionmentioning
confidence: 85%